Arthroscopic Repair of the Anterior Inferior Tibiofibular Ligament - Mette Renate Andersen, M.D., Ph.D.; Lise Benedikte Wendt Ræder, M.D., Ph.D.; Are Haukåen Stødle, M.D., Ph.D. (Arthroscopy Techniques)
Treatment of unstable syndesmosis injuries has traditionally involved a trans-syndesmotic stabilization. Anatomic syndesmotic reduction is important to obtain good clinical results. Open reduction and repair of the anterior part of the syndesmosis is a proposed method to secure anatomic syndesmotic reduction in addition to improving the rotational stability of the ankle mortise. This technical note describes arthroscopic anterior inferior tibiofibular ligament repair using knotless suture anchor fixation and suture button fixation.